Visual antisemitism in Central Europe : imagery of hatred - Hauser, Jakub, 1983-; Janáčová, Eva, 1981-; Day, Barbara, 1944-; Dibble, Graeme; Worthington, Mark, 1966- (De Gruyter Oldenbourg, 2021)
In eleven contributions, Visual Antisemitism in Central Europe, Imagery of Hatred deals with visual manifestations of antisemitism in Central Europe from the Middle Ages to the present day. The publication, which presents heretofore largely unknown materials, seeks responses from diverse perspectives to the question of the role of visuality in the development of antisemitic moods and political agendas that encouraged hatred towards Jews. The scope of visual anti-Judaism and antisemitism always was and still is very wide: from stereotypical depictions that can conceal an underlying message through humorous content, to clearly formulated assaults that aim to escalate animosity towards an imaginary collective enemy. The goal in both these cases is the exclusion of Jews from the majority society imagined as a monolithic whole, and the reification of a dividing line between "us" and "them". With its wide thematic and methodological range, this book offers a comprehensive image of the phenomenon of visual anti-Judaism and antisemitism and provides rich comparative material for the entire Central European region.